Dissecting the effect of Parkinson’s Disease related PINK1 mutations on kinase activity - Gonçalves, Filipa Alexandra Barroso (2016)
Parkinson’s disease (PD), the second most common neurodegenerative movement disorder, affects approximately 2% of the population over 65. At present, there is only symptomatic but no causal cure for PD. Mitochondria are double membrane-bound organelles that are essential for energy production and cellular homeostasis in eukaryotic cells. Defects in this organelle are the underlying cause of several neurological disorders, namely PD. This mitochondrial connection has been furthered strengthened by the identification of mutations in the PINK1 gene that are linked to early-onset recessive PD. PINK1, a mitochondria targeted Ser/Thr kinase, regulates ATP production in healthy mitochondria by phosphorylating Complex I of the Electron Transport Chain. However, in damaged mitochondria PINK1 will phosphorylate Parkin and signal mitochondria for clearance via mitophagy. While understanding the regulation of PINK1 activity is pivotal to interpret how PINK1 executes its different functions in both healthy and damaged mitochondria it still remains unclear how PINK1 induced loss-of-function can affect the kinase activity and the overall (auto)phosphorylation status of PINK1. To scrutinize the impact that the PINK1 clinical mutation have on PINK1 function, we systematically analysed five PD-causing clinical mutations G309D, L347P, E417G, H271Q and W437X. In order access their ability to phosphorylate the known PINK1 substrate Parkin and to (auto)phosphorylate PINK1 an in vitro phosphorylation assay was implemented. To determine their effect towards Parkin recruitment and sequential induction of mitophagy an immunofluorescence techniques was used where staining against Parkin and a mitochondria reside protein was performed. Our results indicate that PINK1 is essential for Parkin recruitment, however the kinase activity is not required for this Parkin-mediated mitophagy pathway.